Effect of Plant Growth Regulator and Media Composition on Growth Budding Planting mukibat Cassava - sutan tarmizi lubis; nini - rahmawati; T - Irmansyah (Jurnal Agroekoteknologi, 2017)
The purpose of research was effect of plant growth regulator and media composition on growth  budding  planting cassava.This research was conducted in the  screen house of  Agriculture Faculty USU (± 25 m asl) from February-April 2016 using factorial group randomized  design  (RAK) with 3 times repitition. The first factor was source of growth  regulators with  four  levels  ie: without  not  giving  the   source  of  ZPT  (P0), coconut  water  50%  (P1),shallot  extract  100%  (P2) and IAA 0.05% (P3) and the second factor was medium on the growth composition goat   manure: top soil: rice husk with three  levels of  treatment  are:  3: 1: 1  (M1),2: 1: 2 (M2) and 1: 1: 1 (M3).The observed parameters was the percentage of success, speed of bud, the bud length, and roots volume. The results of this research showed that the sources of growth regulators affected the speed of germination significantly. The best source of growth regulator treatment was in the level of 50% coconut water. Giving medium on the growth composition significantly affected to the speed germinate and the bud length. The best level of growing media composition is best to goat manuare: top soil: rice husk 3: 1: 1 (M1).  Interactions between source of growth regulators and medium on the growth composition significantly affect the success of percentage parameter, the diameter of bud and amount leaves. Thd best level of combination treatment contained in the shallot extract 100%,  coconut water 50% and growing media composition 3: 1: 1.   Key words : budding, plant growth regulator, the growth composition